Validity and reliability of the persian practice environment scale of nursing work index - Safa Elmi; Hadi Hassankhani; Farahnaz Abdollahzadeh; Mohammad Asghari Jafar Abadi; Judy Scott; Mina Nahamin (Wolters Kluwer Medknow Publications, 2017)
Background: The practice environment pivotal role in patients and nurses better outcomes is evident. Practice Environment Scale of Nursing Work Index (PES-NWI) is widely utilized to assess nursing work environments. The present study was conducted to demonstrate the validity and reliability of the Persian version of PES-NWI. Materials and Methods: The instrument was translated and its psychometrics were investigated by content, construct validity (factor analysis), and homogeneity (internal consistency and intraclass correlation) on a sample of 350 nurses at educational hospitals in East Azerbaijan, Iran. Results: The 30 items loaded onto 4 factors explained 34.95-50.06% of the variance. The items across the factors differed slightly from those reported by the original author of the PES-NWI. Cronbach's alpha and Pearson coefficient for the entire instrument and also for extracted factors was 0.70-0.96. Conclusions: The Persian version of PES-NWI has an appropriate level of validity and reliability in the Iranian setting for nurses. The subscale of Nursing Foundations for quality care needs modification.